Incomplete myocardial rupture following inferolateral myocardial infarction - Maciej Kabaj; Mikołaj Berezowski; Roman Przybylski; Agnieszka Witkowska; Tomasz Brzostowicz; Wojciech Kosmala (Termedia Publishing House, 2020)
A 35-year-old man with no significant past medical history was admitted to the cardiology department with inferolateral ST-elevation myocardial infarction. Coronary angiogram performed immediately after admission (approximately 11-12 hours after the onset of chest pain) revealed right coronary artery occlusion, which was successfully revascularized by percutaneous coronary intervention (PCI) with drug-eluting stent implantation. Postprocedural transthoracic echocardiography showed left ventricular (LV) function abnormalities with ejection fraction reduced to 38%, akinesis of inferior, inferolateral and lateral segments, as well as an aneurysmatic bulge in the inferolateral wall, with wall thickness decreased to 3-4 mm. No pericardial effusion or evidence of cardiac tamponade were found. In view of these findings, urgent cardiac magnetic resonance (CMR) imaging was performed to further explore the morphology of LV wall thinning. This examination revealed incomplete free wall rupture (FWR) encompassing mid inferior, inferolateral and lateral segments (Figures 1 A, B).